Effect of season and stocking density during transport on carcass and meat quality of suckling lambs - Sanchez-Sanchez, M.; Vieira-Aller, C.; De-La-Fuente-Vazquez, J.; Perez-Marcos, C.; Lauzurica-Gomez, S.; Gonzalez-De-Chavarri, E.; Diaz-Diaz-Chiron, M. T. (Spanish Journal of Agricultural Research, 2013)
Many factors related to transport to abattoir affects meat quality, but scarce information is available in suckling lambs. Thus, the aim of this work was to evaluate the effects of season and stocking density on carcass and meat quality of suckling lambs during commercial transport to the abattoir. A factorial design (2 × 3) was used: two seasons (winter and summer) and three stocking densities (SD; 0.08, 0.12 and 0.20 m2 animal-1). Meat quality variables were measured in the M. longissimus at 24 h post-mortem and after 5 days of refrigerated storage. Lambs transported in summer showed lower liver weight (p<0.001), h* (p<0.05), deoxymyoglobin content (p<0.001), pressed juice (p<0.01), shear force (p<0.001) and firmness (p<0.001), and higher initial pH (p<0.001), L*, b*, C* (p<0.001) and a* (p<0.01), as well as metmyoglobin and oxymyoglobin content (p<0.001), than those transported in winter. The effect of season was dependent on storage time, being colour changes more evident at 24 h than after 5 days of storage, whereas lipid oxidation was only observed in stored meat, which may be explain because the natural antioxidative system decreases with time after slaughter. Scarce effect of SD was found on the carcass and meat quality parameters, thus under our experimental conditions the three SD studied appear to be suitable for suckling lambs transport. However, both carcass and meat quality were within the normal commercial range.